Mexico - Low Income Housing : Issues and Options, Volume 1. Main Report - World Bank (Washington, DC, 2013)
This report evaluates the shortcomings of current housing policies, and provides a framework for analysis of alternative policies. Its message is threefold: First, housing has a significant role in terms of basic social support, where the housing unit is a source of capital accumulation, thus a key to expanding Mexico's middle class, from a minority to a majority. Second, the country is facing a two-tiered housing market, those that can afford formal housing, and the near majority who are not served by current federal programs. Third, the housing finance system has amalgamated into multiple institutions, with unclear accountability, and divergent criteria for subsidized credit. The report further reviews the significant challenges facing housing demand, supply, and government intervention, stating that in the absence of viable alternatives, many Mexicans households are under-housed, and suffer from insecure tenure, crowding, and poor quality of housing. This weakness exacerbates poverty, by limiting capital formation, and the role of shelter in improving the asset base of the poor, and, adversely impacts the national economy. The country requires a substantial program of support for low-income housing over the next two decades. In the formal market, reform is necessary to increase effectiveness of current programs so as to open the market to a wider range of private mortgage originators, and investors. And, given the limited fiscal capacity, trade-offs between the scope and depth of support to different segments of the market must be made. Public financial support to the middle market should be incrementally withdrawn, and focused more directly to the poor, requiring a coordinated strategy among public and quasi-public housing agencies to strengthen the market, where a major role for the new Housing Commission would be to oversee implementation of such strategy. Moreover, demand-side subsidies are necessary to support the poor, as well as norms and practices adjusted to foster progressive housing.